Kepemimpinan Yesus Kristus sebagai Model Dasar Kepemimpinan Kristen Berdasarkan Matius 20:20-28 - Firman Panjaitan (IAKN TORAJA, 2020)
Abstract: The leadership crisis is an actual problem in Indonesia, which can be seen from the arrest of several leaders by the Corruption Eradication Commission due to the weak leadership model of the leaders. The leadership of Jesus Christ is the answer to the current leadership crisis. In the midst of a leadership model that relies on power, position and tends to be self-oriented, Jesus' leadership model which is oriented towards a leader-servant pattern and is altruistic in nature becomes the way to answer the leadership crisis. The critical interpretation’s method of the Bible which search for the meaning of the passage based on the existing text and ‘sitz im leben’, especially to Matthew 20:20-28, found a leadership model of Jesus that deserves to be followed and at the same time can be used as a guide for developing an appropriate and effective leadership model. The results of the study show that the leadership model of Jesus Christ in Matthew 20: 20-28 is leadership that has a vision and leadership ethics for the Kingdom of God, namely a leadership model that is pro-people and life (altruistic). Through the leadership model of Jesus Christ, one can lead effectively, efficiently and down to earth. Keywords: Christian; Ethics of the Kingdom of God; Jesus Christ; Leadership; Leader-Servant; Vision. Abstrak: Krisis kepemimpinan adalah masalah aktual di Indonesia, yang terlihat dari peristiwa tertangkapnya beberapa pemimpin oleh Komisi Pemberantasan Korupsi akibat lemahnya model kepemimpinan dari para pemimpin. Menghadapi hal ini, penulis melihat bahwa model kepemimpinan Yesus Kristus merupakan jawaban terhadap krisis kepemimpinan yang sedang terjadi. Di tengah model kepemimpinan yang mengandalkan kekuasaan, jabatan dan cenderung berorientasi pada diri sendiri, maka model kepemimpinan Yesus yang berorientasi pada pola pemimpin-pelayan dan bersifat altruistik menjadi sebuah ‘angin segar’ untuk menjawab krisis kepemimpinan. Dengan menggunakan metode tafsir kritis yang mencari makna perikop berdasarkan teks dan sitz im leben yang ada, khususnya Matius 20:20-28, ditemukan sebuah model kepemimpinan Yesus yang layak diteladani dan sekaligus dapat dijadikan panduan untuk mengembangkan model kepemimpinan yang tepat dan efektif. Hasil penelitian memerlihatkan bahwa model kepemimpinan Yesus Kristus dalam Matius 20:20-28 adalah kepemimpinan yang memiliki visi dan etika kepemimpinan Kerajaan Allah, yaitu model kepemimpinan yang berpihak pada sesama dan kehidupan (bersifat altruistik). Melalui model kepemimpinan Yesus Kristus, seseorang dapat memimpin dengan efektif, efesien dan membumi. Kata Kunci: Etika Kerajaan Allah; Kepemimpinan; Kristen; Pemimpin–Pelayan; Visi; Yesus Kristus